Correlation between chronic kidney disease and all-cause mortality in diabetic foot ulcers: evidence from the 1999-2004 national health and nutrition examination survey (NHANES) - Liang, Jiaru; An, Hang; Hu, Xuyang; Gao, Yuling; Zhou, Jiaqi; Gong, Xiaoyang; Zong, Junwei; Liu, Yong (Frontiers in Endocrinology, 2025)
BackgroundThe poor prognosis of diabetic foot ulcers (DFUs) often leads to amputation and high mortality rates, becoming a heavy economic burden on the healthcare system. Several clinical studies have been conducted to investigate the risk factors for DFU mortality and to provide clinical guidance for better prevention and control of DFU mortality.MethodsWe used R to organize the mortality data of patients with DFU, collected from the NHANES database during the 1994-2004 period, along with three kidney function indicators including Albumin-to-Creatinine Ratio (ACR), estimated Glomerular Filtration Rate (eGFR) and cystatin C, used to assess chronic kidney disease (CKD). We explored the relationship between CKD and the risk of death in DFU patients through multiple kidney function indicators. Baseline characteristics of the surviving group and the mortality group of patients with DFU were analyzed using the ‘svyby’ function in the ‘survey’ package. We used Kaplan-Meier curves, multivariable logistic regression models, Cox proportional risk regression models, and time-dependent ROC curves to analyze the relationship between CKD and the risk of death in patients with DFU.ResultsThis study included a total of 112 patients with DFU. The overall sample had an average age of 65 years, with 43 females (38.39%) and 69 males (61.61%). During the follow-up time, 29 survived and 89 died. All-cause mortality in DFU patients was analyzed based on clinical classifications of ACR, eGFR, and cystatin C, with Kaplan-Meier curves illustrating survival variability. Multivariable logistic regression analysis showed no significant correlation between the risk of death in patients with DFU and CKD. However, analysis of Cox proportional risk regression model that accounted for time effects found a significant association between all-cause mortality and cystatin C levels in patients with DFU. Time-dependent ROC curve analysis demonstrated that cystatin C had superior diagnostic accuracy and stability for predicting all-cause mortality in DFU patients.ConclusionsIn this study, we found that cystatin C demonstrated greater stability and accuracy in assessing the risk of death and predicting mortality in patients with DFU.